The impact of calcification patterns in transcatheter aortic valve performance: a fluid-structure interaction analysis. Issue 4 (29th June 2020) - Luraghi, Giulia; Matas, Jose Felix Rodriguez; Beretta, Marta; Chiozzi, Nicole; Iannetti, Laura; Migliavacca, Francesco
Abstract: Transcatheter aortic valve replacement (TAVR) strongly depends on the calcification patterns, which may lead to a malapposition of the stented valve and complication onsets in terms of structure kinematics and paravalvular leakage (PVL). From one anatomical-resembling model of the aortic root, six configurations with different calcific deposits were built. TAVR fluid-structure interaction simulations predicted different outcomes for the different calcifications patterns in terms of the final valve configuration in the implantation site and the PVL estimations. In particular models with deposits along the cups coaptation resulted in mild PVL, while those with deposits along the attachment line in moderate PVL.